Keanekaragaman Dan Distribusi Makroinvertebrata Di Perairan Hulu Tukad Cangkir Dan Tukad Pakerisan Kabupaten Gianyar - Purusa, I Gede Agus Isha; Arthana, I Wayan; Kartika, I Wayan Darya (Bumi Lestari; Vol 20 No 2 (2020)DO - 10.24843/blje.2020.v20.i02.p04, 2020)
Cangkir and Pakerisan are two rivers which are located in Gianyar-Bali Regency, each with a length of 23 km (54.58 km 2 of watershed area) and 34.5 km (58.33 km 2 of watershed area). These two rivers empties into Lebih Beach that each has a species diversity and abiotic factors. At the upstream of the rivers were occupied by tourism activities that can affect the ecosystem. This study aims to determine the diversity and distribution of macroinvertebrates in the two rivers. Sampling stations were situated at upstream area with 5 stations and 3 replications (15 points) on each river. Sample identification was carried out at the Laboratory of Water Resources Management, Faculty of Marine Science and Fisheries, Udayana University. It was found four species, namely Littorina carinifera , Melanoides torulosa , Parathelphusa convexa , and Bellamya javanica . At upstream of Cangkir and Pakerisan rivers had species of random category distribution pattern with the Morisita Distribution Index value that equal to one. Physical and chemical factors had a major influence on the ecological conditions of the two rivers. The environmental conditions that consisting of substrate type, several physical and chemical parameters were unable to support the life of various biota species found in these aquatic ecosystems.